Synthesis And Study of Antimicrobial Properties of Βeta-Tricalcium Phosphate/Silver Nanoparticles - Saprianti, Siti; Gusrizal, Gusrizal; Syahbanu, Intan (Walisongo Journal of Chemistry, 2024)
Beta-tricalcium phosphate (β-TCP) is a compound used as a basic material for making bio-scaffolds and applied for controlled drug delivery and bone regeneration. This material has the advantages of osteoconductivity and biodegradability. However, this material has weaknesses in its antimicrobial properties, so it requires adding other ingredients to increase its ability, such as NpAg. This research aims to obtain β-TCP/NpAg, which has antimicrobial properties. This research started with NpAg, made β-TCP from a combination of Ca(OH)2 and H3PO4 synthesized β-TCP/NpAg, and tested antimicrobial activity using the disc method. The results of this study show that β-TCP has XRD characteristics in the diffraction pattern, such as 21,541, 25,339, 27,619, 30,881, 32,179, and 34,231. In addition, β-TCP/NpAg has XRD characteristics in the diffraction pattern, such as 25.90, 26.67, 27.95, 29.65, 31.17, 32.61, and 34.47, with the highest peak at 31.17, which is the diffraction pattern of NpAg. The antimicrobial β-TCP/NpAg results showed the ability to inhibit the test microbes by 84.37% on S. aureus, 95.17% on E. coli, and 38.83% on C. albicans.